Implikasi Metode PBL Dalam Peningkatan Hasil Belajar Pendidikan Agama Katolik di SMP Negeri 1 Biatan - Yakobus Gala; Hartutik Hartutik (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study addresses learning challenges, including student learning difficulties and the ineffective use of lecture-based methods, which result in boredom, disengagement, and low student participation. These issues contribute to poor learning outcomes and low completion rates. The aim of this study is to improve student independence and enhance both average scores and the percentage of learning completion by implementing the Problem Based Learning (PBL) model. This aligns with the principles of the flexible Independent Curriculum, which encourages teachers to adopt student-centered learning approaches that enhance outcomes. The study employed a descriptive-qualitative method, structured in two cycles consisting of planning, implementation, evaluation, and reflection. The research involved eight 8th-grade students at SMPN 1 Biatan during the 2024/2025 academic year. The study focused on developing the "independent" dimension of the Pancasila Student Profile (P3), with data collected through behavioral observations and test results at the end of each cycle. Findings showed significant improvements in student independence, with scores increasing from 53 in cycle 1 to 87 in cycle 2. Cognitive achievement levels also improved: the “advanced” category rose from 0% to 63%, “proficient” increased from 25% to 37.5%, while the “feasible” and “newly developing” categories dropped from 37.5% each to 0%. These results suggest that the PBL model positively impacts both character development and academic performance in the context of Catholic religious education, particularly in the topic of the Sacrament of Healing.